Development of Research-Based Science Literacy Learning at State Madrasah Aliyah in Banda Aceh City - Usman, Muzakkar; Idris, Jamaluddin; Yacob, Fakhri; Silahuddin, Silahuddin (AL-ISHLAH: Jurnal Pendidikan, 2024)
The development of research-based learning modules is crucial for enhancing students' scientific literacy, particularly in the context of Islamic educational institutions. This study addresses the need for a validated and practical science literacy module for Physics instruction at State Madrasah Aliyah (Islamic high schools) in Banda Aceh City. This research employed a development research approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to design and validate the learning module. The module underwent a three-stage validation process, including the initial module validity test, a second validation focusing on the content material, and a third test assessing the module’s practicality in classroom use. The findings indicate that the module passed through all three stages of testing with positive results. The module validity, content validity, and practicality were all rated as highly valid by respective validators, including module development experts, content specialists, and practicality assessors. The results suggest that the research-based science literacy module is not only valid in terms of content and structure but also practical for use in Physics instruction. The feedback from validators demonstrates that the module is effective and suitable for teaching purposes. The developed module is highly valid and practical for Physics instruction at State Madrasah Aliyah in Banda Aceh. It is feasible for implementation by Physics teachers to enhance students' scientific literacy in line with the research objectives.